Rad 2(rad 2 +rad 3)-rad 3(2rad 3+rad 2)
,,Rad"=radical....va rog...urgent!!!
Răspunsuri la întrebare
Răspuns de
3
√2(√2+√3)-√3(2√3+√2)=
=2+√6-2·3-√6=2-6=-4
=2+√6-2·3-√6=2-6=-4
Utilizator anonim:
Ups. Editez
Răspuns de
2
√2(√2+√3)-√3(2√3+√2)=
√2×√2+√2×√3-√3×2√3-√3×√2=
√4+√6-2√9-√6=
2+√6-√6-2×3=
2-2×3=
2-6=
-4
√2×√2+√2×√3-√3×2√3-√3×√2=
√4+√6-2√9-√6=
2+√6-√6-2×3=
2-2×3=
2-6=
-4
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă